2013
DOI: 10.1002/ps.3630
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the presence of target-site resistance to neonicotinoids and pyrethroids in Italian populations ofMyzus persicae

Abstract: Target-site resistance to neonicotinoids is common in specialised peach-growing areas, and it is spreading in other Italian regions and on herbaceous hosts. The high frequency of target-site mutations and data obtained from bioassays confirm the presence of multiple resistance mechanisms and suggest the importance of coordinated control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 19 publications
7
96
4
1
Order By: Relevance
“…Two different polymorphisms, giving the same amino acid substitution, were found. The most common is the a/c substitution, already documented in Italian populations of M. persicae ; the other is the a/t substitution, already detected in populations collected in other areas of Southern Europe and Korea and reported here for the first time also in Italy. The presence of the mutation was checked in total in 293 aphids, and the percentage of specimens carrying it was about 20%.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Two different polymorphisms, giving the same amino acid substitution, were found. The most common is the a/c substitution, already documented in Italian populations of M. persicae ; the other is the a/t substitution, already detected in populations collected in other areas of Southern Europe and Korea and reported here for the first time also in Italy. The presence of the mutation was checked in total in 293 aphids, and the percentage of specimens carrying it was about 20%.…”
Section: Resultssupporting
confidence: 66%
“…Interestingly, literature data describe two different polymorphisms responsible for this mutation. In samples collected in France, an a/t nucleotide substitution (atg → ttg) was found only in heterozygous status, whilst in Italian populations an a/c nucleotide substitution (atg → ctg) was described in homozygous status …”
Section: Introductionmentioning
confidence: 94%
“…These evidences indicate that the single point mutation (R81T) obtained in this study should be responsible for the imidaclopridresistance in the field population of A. gossypii. P450-mediated detoxification and target site insensitivity have been confirmed to affect the development of imidacloprid resistance in M. persicae [8,9,23]. However, Kool et al reported that the P450, GST and EST detoxification enzymes have no significant differences between the S and IMI-R strains of A. gossypii, and only the nAChRβ1 R81T point mutation has an effect on the imidacloprid resistance of A. gossypii [4].…”
Section: Discussionmentioning
confidence: 94%
“…Mutations in the nAChR α1 and β2 subunits can cause the resistance of Drosophila melanogaster (Diptera: Drosophilidae) to nitenpyram [7]. A single point mutation (R81T) in the Loop D region of the nAChR β1 subunit was reported in field-resistant populations of Myzus persicae (Hemiptera: Aphididae), and the mutation reduced the sensitivity of pests to neonicotinoids [8,9]. Recently, the mutation (R81T) in the nAChR β1 subunit was reported in a laboratory-selected A. gossypii strain that may confer resistance to imidacloprid [1].…”
Section: Introductionmentioning
confidence: 99%
“…The perceived high efficacy of neonicotinoids against insect pests and related diseases has been demonstrated in several studies ([34]: cabbage stem flea beetle; [35]: pollen beetle; [36]: peach—potato aphid), although others have shown limited efficacy ([37]: peach—potato aphid). For the relatively new groups, oxadiazines and azomethines, the perceived relatively high efficacy against pollen beetle was illustrated in a recent German study [38].…”
Section: Discussionmentioning
confidence: 99%